A Method of Evaluating Residency Training Programs - Goodman, J. T. (1975)
A method for conducting residency program reviews is presented, based on experience with four reviews at McMaster University. The key elements are the stance of the review group as fact finders rather than judges, direct communication with the program director at the beginning and end of the review, and the relatively unbiased perspective which individuals can bring who are ‘internal’ to the university but external to the program being reviewed.